Control interno y gestión de ingresos y gastos en la Municipalidad Provincial de Maynas 2021 - Gonzales Moncada, Manuel Alberto (2022)
The present investigation had as general objective to determine the relationship between internal control and the management of income and expenses in the Provincial Municipality of Maynas, 2021; therefore, a descriptive study - correlational and non-experimental design has been chosen, for which a sample of 25 people has been taken, who were surveyed through a questionnaire. Given this, the following results were achieved that, the internal control in the Municipality is rated as regular (26%), since the Municipality rarely demonstrates to be committed to integrity and ethical values regarding internal control, also, almost Relevant information that can support the development of internal control is never provided, as well as, the municipality seldom identifies the risks that could affect the achievement of the objectives, establishing how they should be managed, then, almost never the control activities are developed Finally, with the purpose of mitigating risks, deficiencies identified in the functioning of internal control are rarely communicated in a timely manner. Likewise, the management of income and expenses is classified as regular (28%), due to the fact that the execution of income rarely makes the corresponding estimates of income, likewise, the files are never issued with the commitment note. The work concludes that internal control is related to the management of income and expenses in a considerable and significant way (rho = .794; sig. = 0.000); in the same way it happens with the execution of income (rho = .828; sig. = 0.000); and the execution of expenses (rho = .755; sig. = 0.000).